The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1094/pdis.1997.81.6.673
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Pepper Vein Banding Virus from Chili Pepper in India

Abstract: A survey conducted in pepper-growing tracts of Karnataka State, covering 165 fields in 33 villages, revealed the occurrence of many pepper mosaic diseases. Based on reactions on selected test plants, the viruses were identified as pepper vein banding virus (PVBV), pepper veinal mottle virus, potato virus Y, cucumber mosaic virus, and tobacco mosaic virus. Among these, PVBV was the most prevalent. PVBV was purified from infected leaves of Capsicum annuum cv. California Wonder. Electron microscopy revealed flexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 11 publications
(4 reference statements)
1
12
0
1
Order By: Relevance
“…This finding is in agreement with Ravi et al, (1997) who compared the N-terminal sequence of PVBV CP with all the potyviral CP sequences and observed the DAG sequence conserved in all aphid-transmitted Potyviruses in the N-terminal sequence of the PVBV CP. Similar observations of conserved DAG motif was also made by Tsai et al, (2008) in all ChiVMV isolates including Indian isolate.…”
Section: Pcr Analysis Of Murda Complex Infected Chilli Plants For Potsupporting
confidence: 92%
“…This finding is in agreement with Ravi et al, (1997) who compared the N-terminal sequence of PVBV CP with all the potyviral CP sequences and observed the DAG sequence conserved in all aphid-transmitted Potyviruses in the N-terminal sequence of the PVBV CP. Similar observations of conserved DAG motif was also made by Tsai et al, (2008) in all ChiVMV isolates including Indian isolate.…”
Section: Pcr Analysis Of Murda Complex Infected Chilli Plants For Potsupporting
confidence: 92%
“…The current study confirmed the incidence of ChiVMV in Naga chilli. The incidence of ChiVMV in C. annum was reported from South India [1,4,6]. To the best of our knowledge, this is the first report and molecular evidence of ChiVMV infection in Naga chilli from North-east India.…”
mentioning
confidence: 69%
“…Earlier, we had reported the purification and characterization of PVBV and showed that it was a distinct member of the genus Potyvirus [16,23]. The NIa protease of PVBV showed 50 and 47% identity with TuMV and TEV NIa protease, respectively.…”
Section: Introductionmentioning
confidence: 95%